If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + 2) = Y Reorder the terms: 4(2 + 5x) = Y (2 * 4 + 5x * 4) = Y (8 + 20x) = Y Solving 8 + 20x = Y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 20x = -8 + Y Combine like terms: 8 + -8 = 0 0 + 20x = -8 + Y 20x = -8 + Y Divide each side by '20'. x = -0.4 + 0.05Y Simplifying x = -0.4 + 0.05Y
| 10-3u=-5u-4 | | 4(x-1)+2x=6(x-6) | | 4s+7t=79 | | -8g=-9g+3 | | p=-5+2p | | 2(5)+3(0)= | | 6x+2x+x+3=39 | | -f=9f+10 | | x^2+2x+y^2+14y-5=0 | | -3(2h-8)=-32-7h | | 6x+10=-3x+109 | | 1-6d=-5d | | 4k=-6 | | 3s+2t=30 | | 4b+6=7b | | -2k+9=-k | | 10x+4=-34 | | x+5=5x+6 | | 4(9-6)+4=2a-6 | | -0.4x+0.5x-9=5 | | -3f=-4f+9 | | 7x+5=-x+5 | | 3n-7(n+3)=7 | | 2[4+x]=-16 | | (4)-(-1)= | | 6u=5u-6 | | -89.0602=10.861b | | 16=8m | | 20x^3+24x^2+4x=0 | | -104=10-6w | | 3(7m+5)+4(3m-8)=148 | | 4(2+5-24)=52-13 |